KONSTRUKSI SOSIAL BUDAYA KERJA DI DINAS PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN ACEH BARAT - Aprinani Aprinani; Yeni Srilestari (Jurnal Society : Pengamat Perubahan Sosial, 2023)
ABSTRACTThe role of the Department of Tourism, Youth and Sports in improving the work culture of employees at the Disparpora, West Aceh District was studied. This research was conducted to understand work culture both in terms of attending or going home discipline and in providing services to the community. The method used is a qualitative method to understand phenomena such as behavior, views, motivations, and attitudes. Data gathering methods utilized in this study include observation, interviews, and documentation. The data used are both primary and secondary data. The Tourism, Youth, and Sports Office of West Aceh Regency is the study's location. The study's findings demonstrate that sociocultural workplace influences, including governmental and economic variables, have an impact on the work culture at the West Aceh District Tourism, Youth, and Sports Service.